Simbol Pukulan Pada Lafadz Dharbah dalam Hadis Riwayat Muslim Nomor Indeks. 2240 (Analisis Teori Semiotika Charles Sander Pierce) - Dini Tri Hidayatus Sya’dyya (AL-MUFASSIR, 2020)
Semiotics is a science that studies the signs and markers, but in studying semiotics we are introduced by several figures who have extensive knowledge, one of whom is Charles Sunder Peirce, an American philosopher, who has very original thoughts among other philosophers, but Peirce has a theory that is so famous with the name triangle theory or often called the triadic theory. This theory is usually used in interpreting a sign that is anywhere. But in this study researchers used Peirce's theory in the Hadith. Where in the Hadith there are also many words and signs that are the same as in the Qur'an. Researchers take the Sahih Muslim Hadith Number 2240 which discusses the blow as a sign and has a meaningful reward.